Molecular basis of viral persistence: a single amino acid change in the glycoprotein of lymphocytic choriomeningitis virus is associated with suppression of the antiviral cytotoxic T-lymphocyte response and establishment of persistence. - Salvato, M; Borrow, P; Shimomaye, E; Oldstone, M (1991)
Isolates of lymphocytic choriomeningitis virus (LCMV) that elicit a cytotoxic T-lymphocyte response (CTL+) have been compared with isolates that suppress the CTL response (CTL-) in an effort to map this phenotype. A single amino acid change in the glycoprotein of the LCMV Armstrong (ARM) strain is consistently associated with the CTL- trait and the ability of the virus to persist (P+). The CTL+ P- parental strain spontaneously gives rise to CTL- P+ variants within lymphoid tissues of mice persistently infected from birth. To map the structural basis of the phenotype, the complete RNA sequence of LCMV ARM 53b (CTL+) was compared with that of its variant ARM clone 13 (CTL-). Differences in 5 of 10,600 nucleotides were found. Three changes are noted in the large L RNA segment, and two are noted in the small S RNA segment. Only two of the changes distinguishing CTL+ from CTL- isolates affect amino acid coding: lysine to glutamine at amino acid 1079 of the polymerase protein, and phenylalanine to leucine at amino acid 260 of the envelope glycoprotein (GP). We also analyzed two additional CTL- variants and four spontaneous CTL+ revertants. All three CTL- variants differ from the original CTL+ parental strain at GP amino acid 260, indicating that this amino acid change is consistently associated with the CTL- phenotype. By contrast the other four mutations in LCMV are not associated with the CTL- phenotype. Sequence analysis of the coding regions of four CTL+ revertants of ARM clone 13 did not reveal back mutations at the GP 260 locus. This finding indicates that the GP 260 mutation is necessary but not sufficient for a CTL- P+ phenotype and that the reversion to CTL+ P- is likely either due to secondary mutations in other regions of the viral genome or to quasispecies within the revertant population that make significant contributions to the phenotype.